Anesthetic Techniques Influence the Induction of Pulmonary Capillary Hemorrhage During Diagnostic Ultrasound Scanning in Rats. (1st February 2015) - Miller, Douglas L.; Dou, Chunyan; Raghavendran, Krishnan
Abstract : Objectives: Pulmonary capillary hemorrhage can be induced by diagnostic ultrasound (US) during direct pulmonary US scanning in rats. The influence of specific anesthetic techniques on this bioeffect was examined. Methods: Ketamine plus xylazine has been used previously. In this study, the influence of intraperitoneal injections of ketamine and pentobarbital, inhalational isoflurane, and the supplemental use of xylazine with ketamine and isoflurane was tested. A diagnostic US machine with a 7.6‐MHz linear array was used to image the right lung of anesthetized rats in a warmed water bath at different mechanical index (MI) settings. Pulmonary capillary hemorrhage was assessed by measuring comet tail artifacts in the image and by morphometry of the hemorrhagic areas on excised lungs. Results: Pulmonary capillary hemorrhage was greatest for pentobarbital, lower for inhalational isoflurane, and lowest for ketamine anesthesia, with occurrence thresholds at MIs of about 0.44, 0.8, and 0.8, respectively. Addition of xylazine produced a substantial increase in hemorrhage and a significant proportion of hemorrhage occurrence for ketamine at an MI of 0.7 ( P < .01) and for isoflurane at an MI of 0.52 ( P < .01). Conclusions: Ketamine plus xylazine and pentobarbital yield lower thresholds than ketamine or isoflurane alone by nearly a factor of 2 in MI. These results suggest that the choice of the anesthetic agent substantially modifies the relative risks of pulmonary capillary hemorrhage from pulmonary US.